Study of pattern of nosocomial infections among post-operative patients following obstetrical and gynaecological surgeries in a tertiary care institute of northern India - ., Latika; Nanda, Smiti; Dahiya, Pushpa; Chaudhary, Sushila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hospital acquired infections (HAIs) are the major causes of morbidity and mortality, functional disability and financial burden among the patients admitted in hospitals. The nosocomial infection has thrown a big challenge to the health sector in both the developing and developed countries; therefore, it is important to put in place surveillance system for monitoring its incidence rate and planning early interventions for its prevention. The aim and objective of the study was to study the socio demographic profile of the patients who underwent Obstetrical and Gynecological surgeries and to identify the risk factors and causative organisms associated with the post-operative nosocomial infection and pattern of antibiotics sensitivity. Methods: It was a record based retrospective study carried out in a tertiary care referral institute. The case files of all post-operative patients from January 2015 to July 2015 were retrieved from the Medical Record department and an extensive analysis was carried out. Results: It was found that majority of the patients (75%) with nosocomial infection were in the age group of 20-35 years and all were married. Most of them (72%) were from the rural background. It was observed that around 9% patients reported nosocomial infection after emergency laparotomy procedure as compared to 8% of patients after elective procedure. Conclusions: In this study it was found that surgical site infection (SSI) was most common nosocomial infection followed by Urinary tract infection. The majority of surgical site infections can be prevented by the preoperative, intraoperative and postoperative phases of care.